A ANALISIS NILAI-NILAI SOSIAL DALAM KEGIATAN SABTU BUDAYA UNTUK MENINGKATKAN KREATIVITAS SISWA DI SEKOLAH DASAR NEGRI 1 MASBAGIK TIMUR KECAMATAN MASBAGIK LOMBOK TIMUR - Nurmayanti; Zalia Muspita; Andi Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze social values ​​in cultural Saturday activities to enhance student creativity at SDN 1 Masbagik Timur for the 2024/2025 Academic Year. This study employed qualitative research, employing descriptive qualitative methods. Data sources were collected from the principal, teachers, and students of SDN 1 Masbagik Timur. The researcher analyzed data using three data collection techniques: observation, interviews, and documentation. Based on the results of the study, the analysis of social values ​​in cultural Saturday activities to enhance student creativity at SDN 1 Masbagik Timur. 1) Demonstrates the social values ​​developed through cultural Saturday activities. Cultural Saturday activities at SDN 1 Masbagik Timur play an important role in instilling and developing social values ​​in students from an early age. Values ​​such as mutual cooperation, cooperation, tolerance, discipline, responsibility, honesty, and empathy can be developed through various activities carried out, such as making crafts, maintaining environmental cleanliness, preparing art performances, to wearing regional clothing. 2) Social values ​​in cultural Saturday activities towards increasing student creativity that Cultural Saturday activities at SDN 1 Masbagik Timur play an important role in integrating the development of social values ​​with increasing student creativity. Values ​​such as cooperation, responsibility, and mutual respect are proven to encourage students to be more confident, active, and brave in expressing ideas in the form of works of art, performances, and other creative activities. School support through the provision of facilities, teacher mentoring, and freedom of expression creates a positive atmosphere that fosters student collaboration and innovation. 3) Supporting and inhibiting factors in the application of social values ​​through Cultural Saturday activities. Based on the results of the study, supporting factors for the implementation of Cultural Saturday activities at SDN 1 Masbagik Timur include full support from the principal and teachers, student enthusiasm, and active participation of parents in preparing activity needs. The availability of facilities such as art equipment, costumes, and open spaces, as well as a school environment that respects cultural diversity, contributed to the success of this activity. However, several inhibiting factors remained, including limited practice time, a lack of equipment and costumes, a lack of understanding of the activity's objectives on the part of some students, low self-confidence, and a lack of cooperation among some students, all of which hindered the smooth running of the practice process.